Development of Self and Career-Understanding Gamification-Assisted Media for Students with Disabilities - Abdillah, Husni; Setyosari, Punaji; Muslihati, M; Hambali, IM; Dewanti, Septinda Rima (KONSELOR, 2023)
The objective of this study is to develop a career advice platform for Children with Special Needs (CSN) through the use of gamification-assisted education. The study suggests that inclusive vocational schools in Surabaya and Sidoarjo, East Java, should create an Android application called GOPEKA in response to the dearth of structured employment services and specialized resources for CSN. For CSN, who have a predisposition for studying via Android applications, the program is both user-friendly and captivating. The ADDIE paradigm, which comprises Analysis, Design, Development, Implementation, and Evaluation, was specifically applied in our Research and Development (R&D) endeavors. An essential component of career coaching for CSN, gamification-assisted media emerged from an initial investigation that included a literature review and conversations with school counsellors. Utilizing the Career Information Processing and Career Diamond theories as core concepts and incorporating gamification features (components, mechanics, dynamics) were also highlighted in the literature review. A GOPEKA application prototype was developed during the design and development process. Its interface design and button performance were enhanced as a result of a validation procedure conducted by professionals and experts. Seven secondary schools, including a special needs high school in Surabaya and Sidoarjo, participated in an evaluation of the app's efficacy with 82 disabled students from vocational high schools. The average total career planning scores improved significantly from the pre-test to the post-test subsequent to utilizing the GOPEKA application, as determined by the Wilcoxon test on non-normal data distribution. The study's findings indicate that the GOPEKA application's second iteration is efficacious and appropriate for implementation with CSN, subsequent to its validation and feasibility assessments. In addition, the article proposes avenues for further research and addresses the constraints associated with the implementation of gamification in product development.